Substitute Heirs : an Overview from Perception and Role Of Ustad in Bengkulu, Indonesia - Yusmita Yusmita; Adnan Ahmed Usmani (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
Legal rules regarding substitute heirs are regulated in Article 183 of the Compilation of Islamic Law, which stipulates that heirs who die earlier than heirs can be replaced by their children. Ideally, this rule of law has been disseminated to the community. Ustadz is an officer who directly delivers Islamic laws to the community. The type of this research is descriptive-qualitative research. The research subjects were Ustad who gave religious lectures to taklim assembly in Bengkulu City and the congregation of the taklim assembly. Data collection techniques using interviews. From the results of the study, it can be seen that the majority of Ustad in Bengkulu City do not master Islamic inheritance material, especially the rules regarding substitute heirs. Because of that they rarely convey inheritance material to the public. Regarding the role of Ustad in Bengkulu City in socializing the rules for substitute heirs, they have not played much of this due to several factors. The first factor is that they don't know much about the Islamic inheritance system, especially about the rules of surrogate heirs. Because of that, they did not convey this material to the public. The second factor, the community did not ask them about inheritance problems because they were not interested in studying it more deeply. The third factor, most people use adat in resolving the distribution of inheritance, and if there is a dispute, it is resolved by custom, then the Islamic inheritance rules regarding inheritance distribution, especially substitute heirs, are not a requirement for Bengkulu City Muslims. The institution responsible for disseminating legal regulations that regulate Indonesian Muslims is the Ministry of Religion